Cognitive and non‐cognitive factors in educational and occupational outcomes—Specific to reading disability?. (25th November 2020) - Kortteinen, Hanna; Eklund, Kenneth; Eloranta, Anna‐Kaija; Aro, Tuija
Abstract : Low education and unemployment are common adult‐age outcomes associated with childhood RD (c‐RD). However, adult‐age cognitive and non‐cognitive factors associated with different outcomes remain unknown. We studied whether these outcomes are equally common among individuals with c‐RD and controls and whether these outcomes are related to adult‐age literacy skills or cognitive and non‐cognitive factors or their interaction with c‐RD. We examined adult participants with c‐RD ( n = 48) and their matched controls ( n = 37). Low education was more common among c‐RD than the controls, whereas long‐term unemployment was equally common in both groups. Moreover, adult‐age literacy skills, cognitive skills and non‐cognitive factors were related to both low education and long‐term unemployment. Only a few c‐RD‐specific associations emerged: c‐RD, especially in interaction with low verbal or reading comprehension, was associated with low education, and c‐RD in interaction with slow adult‐age reading was associated with long‐term unemployment. Avoidant coping style, emotional wellbeing and social functioning were related to education, and life‐satisfaction to unemployment irrespective of c‐RD. Thus, the non‐cognitive factors associated with education and employment are similar in individuals with and without c‐RD. Special attention should be paid to training c‐RD individuals in basic academic, social and emotional skills.